(untitled) (Transport systems and technologies, 2020)
Documentation of the OCPP protocol version 1.6 was investigated. A comparative analysis of the implementation of this protocol using SOAP and JSON was carried out. It showed that it is advisable to select OCPP JSON Specification to model the interaction of an electric vehicle with a charging station. Functional requirements for client-side and server-side software was identified. The Precedence Diagram was constructed. The C# programming language, Windows Forms technology and the Visual Studio integrated development environment were chosen to implement the functional part. The basic protocol is Websocket using JSON files. WPF technology uses a declarative XAML markup language. With these tools, an application design was created on both client and server sides. Frame animation was developed in the Adobe Photoshop graphics editor. After combining the functional and visual parts, a workable application of the simulation of the interaction of the electric vehicle with the charging station was obtained. Many development scenarios were considered during the development: charging the electric vehicle in a positive scenario (working server, available port), processing such negative usage scenarios as a non-working server, or trying to start charging on an inaccessible port, or trying to disconnect in the unfinished charging process, etc. Ready-to-use application can be used to demonstrate the protocol and the charging process of an electric vehicle from a charging station.